2013
DOI: 10.1073/pnas.1313446110
|View full text |Cite
|
Sign up to set email alerts
|

Mining the O-mannose glycoproteome reveals cadherins as major O-mannosylated glycoproteins

Abstract: The metazoan O-mannose (O-Man) glycoproteome is largely unknown. It has been shown that up to 30% of brain O-glycans are of the O-Man type, but essentially only alpha-dystroglycan (α-DG) of the dystrophin-glycoprotein complex is well characterized as an O-Man glycoprotein. Defects in O-Man glycosylation underlie congenital muscular dystrophies and considerable efforts have been devoted to explore this O-glycoproteome without much success. Here, we used our SimpleCell strategy using nuclease-mediated gene editi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
187
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(203 citation statements)
references
References 44 publications
4
187
2
Order By: Relevance
“…Analysis of the identified proteins revealed that a large proportion (n = 83, 29%) were known or predicted nuclear and/or cytosolic proteins without recognizable signal peptides. This finding was in striking contrast to our previous analysis of the O-Man glycoproteome of human cells, where all identified glycoproteins were known or predicted to traffic the secretory pathway (16). We therefore also inspected all identified glycoproteins with signal peptides for the specific localization of O-glycosites with respect to known or predicted membrane orientation and found sites predicted to be located in the cytosolic compartment (Dataset S1).…”
Section: Resultscontrasting
confidence: 61%
See 4 more Smart Citations
“…Analysis of the identified proteins revealed that a large proportion (n = 83, 29%) were known or predicted nuclear and/or cytosolic proteins without recognizable signal peptides. This finding was in striking contrast to our previous analysis of the O-Man glycoproteome of human cells, where all identified glycoproteins were known or predicted to traffic the secretory pathway (16). We therefore also inspected all identified glycoproteins with signal peptides for the specific localization of O-glycosites with respect to known or predicted membrane orientation and found sites predicted to be located in the cytosolic compartment (Dataset S1).…”
Section: Resultscontrasting
confidence: 61%
“…An additional 4 U PNGase F was added and incubated at 37°C for 4 h. The digests were acidified with 12 μL TFA, incubated at 37°C for 20 min, cleared by centrifugation at 10,000 × g for 10 min, and purified by Sep-Pak C18 (Waters) columns. The LWAC protocol for isolation of O-Man glycopeptides was as previously described (16). Sep-Pak-purified peptides were concentrated by evaporation, and the reduced solution was diluted with an equal volume of 2 × ConA buffer A (40 mM Tris·HCl, pH 7.4, 300 mM NaCl, 2 mM CaCl 2 /MgCl 2 / MnCl 2 /ZnCl 2 , 1 M urea) before loading in a 2.8-m-long ConA lectin agarose column.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations